Democracy in modern Spain - Gunther, Richard (Yale University Press, 2004)
"This book, written by three of the world's leading experts on Spanish politics, is the first comprehensive study of the origins and basic character of Spain's democratic political system. It presents rigorous analyses of the regime's core political institutions (including the profound decentralization of the state that has unfolded over the past two decades), its political parties and party systems, patterns of electoral behavior, the evolution of Spain's political culture, and the impact of these social and institutional changes on public policy processes and outputs." "Richard Gunther, Jose Ramon Montero, and Joan Botella begin by discussing those aspects of Spanish society and politics that had contributed to "Spanish exceptionalism"--Most notably, the country's inability to sustain a stable and democratic regime prior to the 1970s. They assert that the successful transition to and consolidation of democracy was made possible by socioeconomic modernization, cultural change (including depolarization and secularization of Spanish society), and crucial decisions made by political elites concerning the establishment of core democratic institutions and norms of political behavior that rejected the rancor and intolerance of previous eras. Based on more than 500 hours of interviews with key political elites (under both the Franco regime and the current democracy), extensive analyses of public opinion and electoral behavior surveys, and other original research, the book sheds important new light on Spain's democractic regime and its key institutions."--Jacket